Identification of a descriptive beam size metric for complex beam shapes - Chechik, Lova; Schmidt, Michael (Procedia CIRP, 2024)
Traditionally, in laser processing, simple beam profiles such as Gaussian beam profiles or top-hat profiles have been widely used. Recently, more complex beam shapes have been theorised. A common question remains: which factors affect the process most significantly? The size of the laser beam or its energy distribution – and how can the size of a complex beam shape be defined? In this work, Rosenthal-style calculations are used to calculate the conduction-mode temperature fields resulting from various laser beam shapes. Commonly used methods are used to calculate the beam size, such as the second moment method and the 1/e2 method, correlating them with calculated melt pool dimensions. Using these methods, we investigate whether a single beam size metric is sufficient to provide insights into conduction-mode laser processing.<br
Keywords: Beam Shaping; Laser Processing